2015
DOI: 10.1186/s12245-015-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Burden of motorcycle-related injury in Malaysia

Abstract: BackgroundRoad traffic injury (RTI) contributes to major morbidity and mortality in both developed and developing countries. Most of the injuries are caused by road-related injuries that specifically relate to motorcycle crash. We attempted to conduct a short survey to determine the magnitude of burden related to motorcycle-related RTIs in Malaysia. We hypothesize that motorcycle-related RTI in Malaysia contributes significantly to the health burden in the country.MethodsThe cross-sectional survey involves dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 5 publications
1
19
0
3
Order By: Relevance
“…Consistent with past findings, 34,53,54,55,56 head trauma remained as a strong indicator of adverse outcome for injured geriatric trauma patients. While injury to extremity region was reported as the most common part of injured region following road traffic accidents in general population, 57,58,59,60,61 a substantial number of head injury cases were reported among geriatric trauma patients in this study. This implied that the mandatory road safety practices such as wearing safety or crash helmet, wearing seatbelt and presence of functional airbag were not sufficiently being emphasized among elderly road users.…”
Section: Discussionmentioning
confidence: 54%
“…Consistent with past findings, 34,53,54,55,56 head trauma remained as a strong indicator of adverse outcome for injured geriatric trauma patients. While injury to extremity region was reported as the most common part of injured region following road traffic accidents in general population, 57,58,59,60,61 a substantial number of head injury cases were reported among geriatric trauma patients in this study. This implied that the mandatory road safety practices such as wearing safety or crash helmet, wearing seatbelt and presence of functional airbag were not sufficiently being emphasized among elderly road users.…”
Section: Discussionmentioning
confidence: 54%
“…(22) This situation is similar to that in Malaysia, where 70% of accident victims are motorcycle drivers. (10) The results of our study showed that in general the proportion of severity of injury due to land transportation was 8.8%. Based on transportation mode, it is apparent that the proportion of severity of injury due to motorcycles was significantly higher as compared with other land transportation modes.…”
Section: Discussionmentioning
confidence: 69%
“…Death due to injury from motorcycle transportation involving drivers and passengers account for 58.7%. (10) The results of a study in Kenya show that motorcycles as a mode of public transport are the main cause of severity and death due to injury. (11) There are three main principles in the prevention and control of injury, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also reported that the increasing of the mortality-rate might be a result of recent economic changes, a rapid increase in motorization rates, and a lack of public transportation policies oriented to the need of discouraging the use of private vehicles [6,7]. In addition, factors such as the growth in motorcycle sales, higher cost of fuel for regular 4-wheels vehicles, and the generalized idea-along with the misleading conception that motorcycles are more environmental friendly (among others) have also been related to this increasing phenomenon [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%